1999
DOI: 10.1016/s0034-5687(99)00041-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and respiratory reflexes: the tropical fish, traira (Hoplias malabaricus) O2 chemoresponses

Abstract: To determine the location and distribution of chemoreceptors involved in the cardiovascular and respiratory responses to hypoxia of traira (Hoplias malabaricus), we measured heart rate, arterial blood pressure, ventilation frequency and amplitude of opercular movements during exposure to hypoxia and application of NaCN to either water bathing the gills (external) or the ventral aortic blood (internal). This was done before and after selective denervation of branchial branches of the IXth and Xth cranial nerves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 22 publications
5
55
0
1
Order By: Relevance
“…However, the progressive denervation had no significant effect on any of the respiratory variables, suggesting that there is no significant sensory input arising from the gills under normoxic, normocarbic conditions modulating respiratory drive. Similar observations have been made by others on other species (Sundin et al, 1999;Reid et al, 2000). …”
supporting
confidence: 92%
See 1 more Smart Citation
“…However, the progressive denervation had no significant effect on any of the respiratory variables, suggesting that there is no significant sensory input arising from the gills under normoxic, normocarbic conditions modulating respiratory drive. Similar observations have been made by others on other species (Sundin et al, 1999;Reid et al, 2000). …”
supporting
confidence: 92%
“…Those eliciting reflex increases in f R appear to be located on all gill arches in traíra and tambaqui while those eliciting reflex increases in V AMP in traíra may be located elsewhere in the orobuccal cavity Sundin et al, 2000) as has also been suggested for extra-branchial O 2 chemoreceptors (Hughes and Shelton, 1962; Butler et al, 1977;Sundin et al, 1999). While exposure to 5% CO 2 stimulated ventilation in jeju, exposure to higher levels of CO 2 in the water led to a significant reduction in gill ventilation.…”
Section: Hypercarbic Respiratory Reflexes In Jejumentioning
confidence: 87%
“…Different NaCN concentrations were assessed to determine the lowest concentration that gave clear responses for each animal, and then the same concentration was used after MK801 treatment. The chosen concentrations lie within range of previous studies (Burleson and Smatresk, 1990;Sundin et al, 1999Sundin et al, , 2000. The hypoxic period started when nitrogen bubbling of the respiratory water was turned on, resulting in a PO∑ drop from 19 kPa to 5 kPa within the 10 min exposure period.…”
Section: Experimental Protocolsmentioning
confidence: 62%
“…There are several reports that fish possess both internal and external oxygen receptors (Burleson and Milsom, 1993;Milsom and Brill, 1986) and that they may elicit different cardiorespiratory responses (Milsom 1996;Milsom et al, 2002;Sundin et al, 1999), so we used injection of NaCN into the respiratory water and intra-arterially to determine whether the sculpin showed any differences in their cardiorespiratory reflexes depending on the type of oxygen chemoreceptor group being stimulated. Overall there was no difference between the external (water) and internal (blood) NaCN-elicited cardiorespiratory responses other than that NaCN applied to the respired water significantly increased the ventilation amplitude and produced a more marked bradycardia.…”
Section: Discussionmentioning
confidence: 99%
“…Na necessidade de anestesia mais prolongada para o pirarucu, um sistema de aspersão intermitente de anestésico nas brânquias pode ser interessante, de forma que assim seria possível saturar as lamelas com anestésico sem riscos de afogamento do peixe pulmonado. Comparativamente, mesas cirúrgicas, utilizadas em estudos de fisiologia em peixes de respiração branquial, são equipadas com sistemas de minireservatórios, bombas e tubulações de diâmetro reduzido, que irrigam as brânquias com soluções anestésicas durante os procedimentos cirúrgicos, que duram de 15 a 20 minutos aproximadamente (SUNDIN et al, 1999). O teste de outros produtos anestésicos como a benzocaína, a tricaína metanosulfonato (MS222) e o metomidato, bem como a prova de indução à anestesia por injetáveis (por exemplo, xilazinas) e inaláveis (por exemplo, halotano e óxido nitroso), é ainda necessária para o pirarucu.…”
unclassified